Effect of aerial application of adjuvants on pepper defoliant droplet deposition and efficacy of defoliation sprayed by unmanned aerial vehicles - Liu, Yapeng; Xiao, Qinggang; Han, Xiaoqiang; Zeeshan, Muhammad; Fang, Zhihao; Dou, Zechen (Frontiers in Plant Science, 2022)
Defoliant spraying is an important aspect of the mechanized processing of pepper harvesting. Complete and uniform spraying of defoliant could improve the quality of defoliation and reduce the impurity content in processing pepper. In this study, we assessed the effect of aerial spraying of adjuvants on physicochemical properties of defoliant solution and droplet deposition when using an unmanned aerial vehicle (UAV) for defoliation spraying. The results showed that Puliwang was a better aerial spray adjuvant suitable for spraying defoliants for processing pepper using UAVs, with a higher defoliation rate and better droplet deposition. Although the YS-20 adjuvant had a higher droplet deposition amount (0.72 μg/cm2) in the middle layer, its performance was poor in droplet size, density, and coverage. The size and density of the droplets added with the Manniu were basically the same as the Puliwang, even the distribution uniformity was better (the CV of the upper canopy layer was only 33.6%), but the coverage rate was poor. In the treatment with AS-901N, there was no marked increase in droplet size, so evaporation and drift were not improved, eventually resulting in a lower defoliation rate. Puliwang had the highest comprehensive score, followed by AS-910N, YS-20, and Manniu.